Breast imaging using 3D electrical impedance tomography - Prasad, Sachin N; Houserková, Dana; Campbell, Jan (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2008)
Aim: To determine the diagnostic efficiency of 3D Eletrical Impedance Tomography (EIT) compared toMammography (MG) and Ultrasonography (USG) in imaging the breast.Materials and Methods: A group of 88 patients presenting with various breast complaints was examined usingcombined Mammography and Ultrasonography (MG & USG) or either of these modalities alone. The same patientswere then examined using the 3D EIT imaging system “MEIK”.The fi ndings were then compared. The sensitivity of these modalities for this group of patients were later determinedand statistically analysed. Results: Of the total of 88 patients, 59 fi ndings were “suspicious” by any of the 3 modalities alone or by their combination.EIT had a sensitivity of 77.8 % compared to MG with a sensitivity of 83.3 % and USG with a sensitivity of94.4 % regarding cases of fi brocystic mastitis. For cases involving cysts, EIT had 100 % sensitivity which was the sameas that for USG compared to MG with a sensitivity of only 81 %. Among cases of fi broadenoma, EIT had a sensitivityof just 68.8 % compared to MG with a sensitivity of 87.5 % and USG with a sensitivity of 75 %. Finally among cases ofcarcinoma, EIT had a sensitivity of 75 % compared to the sensitivity of 100 % of MG and USG in our group of patients.The study revealed that there was no overall signifi cant diff erence in sensitivity between MG-USG (p = 0.219) andMG-EIT (p = 0.779) and USG-EIT (p = 0.169). However, in regard to identifying cysts there was signifi cant diff erencein the sensitivity of MG compared to USG & EIT suggesting that EIT has a role in these cases.Conclusion: Electrical impedance could be used as an adjunct to Mammography and Ultrasonography for breastcancer detection. However, the diff erentiation of malignant from benign lesions based on impedance measurementsneeds further investigation. Multifrequency electrical impedance imaging appears the most promising for detectingbreast malignancies but methodological improvements need to be made to realise its potential.
Keywords: dospělí; tomografie; Statistics as Topic; nádory prsu; Female; statistika jako téma; zobrazování trojrozměrné; Imaging, Three-Dimensional; Adult; ženské pohlaví; Mammography; lidé; mamografie; Sensitivity and Specificity; Breast Neoplasms; senzitivita a specificita; Ultrasonography, Mammary; Evaluation Studies as Topic; elektrická impedance; hodnotící studie jako téma; Tomography; ultrasonografie prsů; Electric Impedance; Humans